2021
DOI: 10.3389/fphar.2021.724141
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Autophagy Prevents the Development and Progression of Peritoneal Fibrosis

Abstract: Peritoneal fibrosis (PF) is a major cause of ultrafiltration failure in long-term peritoneal dialysis (PD) patients. Nevertheless, limited measures have been shown to be effective for the prevention and treatment of PF. Some views reveal that activation of autophagy ameliorates PF but others demonstrate that autophagy promotes PF. It is obvious that the role of autophagy in PF is controversial and further studies are needed. Here, we investigated the role of autophagy in rat models of PF and damaged cultured h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Immunohistochemical and immunofluorescence staining were carried out according to the procedure described in our previous study ( 32 , 33 ). FFPE sections (3 μm) were rehydrated and incubated with primary antibodies against α-SMA (1:100, ab5694, Abcam), Twist (1:100, ab175430, Abcam), HDAC6 (1:100, A11259, ABclonal), CD163 (1:100, GB11340-1, Servicebio), Collagen I (1:400, GB11022-3, Servicebio), CD68 (1:100, sc-20060, Santa Cruz Biotechnology) and Arginase-1 (1:100, #93668, Cell Signaling Technology), and then secondary antibodies (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical and immunofluorescence staining were carried out according to the procedure described in our previous study ( 32 , 33 ). FFPE sections (3 μm) were rehydrated and incubated with primary antibodies against α-SMA (1:100, ab5694, Abcam), Twist (1:100, ab175430, Abcam), HDAC6 (1:100, A11259, ABclonal), CD163 (1:100, GB11340-1, Servicebio), Collagen I (1:400, GB11022-3, Servicebio), CD68 (1:100, sc-20060, Santa Cruz Biotechnology) and Arginase-1 (1:100, #93668, Cell Signaling Technology), and then secondary antibodies (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…In long-term PD, autophagy promotes fibrosis and apoptosis in the peritoneum [ 184 ]. In two different murine models of PDFs and CG damage, autophagy was found highly activated [ 185 ]. In these models, autophagy inhibition with 3-methyladenine (3-MA) successfully prevented peritoneal damage, noted by downregulation of TGF-β/SMAD signaling and the EMT transcription factors Slug and Snail, repressed activation of epidermal growth factor receptor (EGFR)/extracellular signal-regulated protein kinases ½ (ERK1/2) signaling pathway, decreased STAT3/NF-κB-mediated inflammatory response and macrophage infiltration, and prevented β-catenin-mediated peritoneal angiogenesis [ 185 ].…”
Section: Potential Anti-inflammatory Treatments In the Preservation O...mentioning
confidence: 99%
“…Autophagy plays an important role in maintaining the homeostasis, and it can regulate the development and differentiation of specific cells, such as adipocytes and lymphocytes ( 11 ). However, studies have reported that autophagy is also involved in pathological mechanisms ( 12 , 13 ). Using autophagy inhibitor 3-methyladenine (3-MA), our previous research has indicated that inhibition of autophagy alleviated HN in an adenine (0.1 g/kg) and potassium oxonate (1.5 g/kg)-induced rat model and an in vitro model of uric acid stimulated cultured rat renal interstitial fibroblasts (NRK-49F).…”
Section: Introductionmentioning
confidence: 99%